MiR-486-5p-directed MAGI1/Rap1/RASSF5 signaling pathway contributes to hydroquinone-induced inhibition of erythroid differentiation in K562 cells. (August 2020) - Ma, Xiaoju; Zhang, Xue; Luo, Jiao; Liang, Boxuan; Peng, Jing; Chen, Chuanying; Guo, Hongyu; Wang, Qing; Xing, Xiumei; Deng, Qifei; Huang, Hehai; Liao, Qilong; et al.
Abstract: Bone marrow failure is a characteristic effect of benzene exposure. Our previous study has shown that miR-486-5p is involved in benzene induced-suppression of erythroid differentiation. However, the mechanism of miR-486-5p to initiate the above process remains unclear. In this study, we used miRTar software to predict putative miRNA targets and pathway. We found that miR-486-5p may target Ras-associated protein-1 (Rap1) signaling pathway-associated genes. Our in vitro study further showed significant dose-dependent upregulation of MAGI1 and RASSF5 expressions in hydroquinone (HQ)-induced suppression of erythroid differentiation of K562 cells. Over-expression or down-regulation of miR-486-5p altered MAGI1 and RASSF5 expression and modified erythroid differentiation. Dual-luciferase reporter assay and fluorescence-based RNA electrophoresis mobility assay (FREMSA) further confirmed that miR-486-5p directly bound to the 3′-untranslated region (3'-UTR) of MAGI1 and RASSF5 . In addition, the expressions of RAPGEF2 and RAP1A, which are downstream genes of MAGI1, were also significantly increased when HQ inhibited erythroid differentiation. Knockdown of MAGI1 reversed HQ-induced inhibition of erythroid differentiation via downregulation of RAPGEF2, RAP1A and RASSF5 . Together, these data indicate that miR-486-5p directly targets MAGI1 and RASSF5 and integrates with Rap1 signaling to modify HQ-induced inhibition of erythroid differentiation in K562 cells. Highlights: HQ inhibits erythroid differentiation of K562 cells by down-regulation of miR-486-5p. MiR-486-5p targets MAGI1 and RASSF5 leading to HQ-induced inhibition of erythroid differentiation in K562 cells. MiR-486-5p-directed Rap1 signaling pathway plays a critical role in HQ-inhibited erythroid differentiation of K562 cells.